TGF-β Induces Wnt10b in Osteoclasts From Female Mice to Enhance Coupling to Osteoblasts - Ota, Kuniaki (Endocrine Society, 2013)
In young adults, bone lost through osteoclast-mediated resorption is precisely replaced in both location and amount. Understanding how these two processes are coupled is crucial to advancing treatments for osteoporosis, a disease that progresses when the processes become uncoupled. We documented that osteoclasts secrete the mammalian integration 1 gene that is the homolog of Drosophila Wngless (Wnt) 10b, bone morphogenetic protein 6 (BMP6), and the chemokine sphingosin 1 phosphate (S1P) to promote mesenchymal cell mineralization in vitro. During bone resorption, TGF-β1 is released from the bone extracellular matrix and activated by osteoclasts. Thus, TGF-β1 levels are elevated during the resorption phase of bone turnover. We therefore investigated the influences of TGF-β1 on osteoclast-mediated support of mineralization. TGF-β1 increased osteoclast production of Wnt10b, but not BMP6 or S1P. Blocking Wnt10b activity with the Wnt signaling inhibitor Dickkoph-related protein 1 suppressed the ability of TGF-β–treated osteoclast-conditioned media to promote osteoblast mineralization. Examination of TGF-β signaling in osteoclasts revealed that induction of Wnt10b expression was dependent on Smad2/3 activation and independent from TGF-β1 stimulation of protein kinase B (AKT) or MAPK kinase. TGF-β1–treated osteoclast-conditioned media from cells with blocked Smad signaling exhibited a reduced ability to support mineralization, demonstrating the importance of Smad signaling in this response. Parallel cultures with suppressed TGF-β activation of AKT or MAPK kinase signaling retained their ability to elevate mineralization. These results demonstrate that TGF-β1 stimulates Wnt10b production in osteoclasts, which may enhance restoration of the bone lost during the resorptive phase of bone turnover.